The Depiction of Coconut Products (Food and Non-Food) In Tidore Islands, North Maluku - Nurhasanah Nurhasanah; Angela Wulansari; Hamidin Rasulu; Suryati Tjokrodiningrat; Johan Fahri; Suwito Suwito; Nahu Daud; Husen Alting (Food, Agriculture and Natural Resources - NETWORKS, 2021)
Indonesia is the highest producer of coconut in the world. One of the cities in Indonesia which is the central producer of coconut is Tidore Islands, North Maluku. Tidore Islands is a city in the east part of Indonesia located in the province of North Maluku. Tidore Islands has many products made of coconut tree parts as raw materials. The products are varied from food products to non-food products. This research was a descriptive study to discover the variety of coconut products produced in the Tidore Islands as basic data to develop an integrated coconut industry in the Tidore Islands. The research was conducted in 4 sub-districts that had >40 ton/year production of coconut. The result showed that black copra was the main product of coconut widely produced by people in the Tidore Islands. Other food products were white copra, coconut oil, and VCO. Non-food products widely produced by people in Tidore Island were coconut shell charcoal, coconut fiber, broomstick, and liquid smoke.